PERCEPTION OF NET BENEFITS OF ELECTRONIC MEDICAL RECORDS AND ITS IMPACT ON THE EFFECTIVENESS OF POLY-CARE SERVICES IN HOSPITAL - Mochammad Malik Ibrahim; Risna Zubaidah; Dhian Ika Prihananto (Rena Cipta Mandiri, 2026)
The digitization of medical records in hospitals was developed to support the quality and effectiveness of services through more systematic, rapid, and integrated patient data management. However, in its implementation, the utilization of this system has not fully achieved optimal results due to various technical and operational obstacles that still affect the smoothness of services and the level of benefits perceived by users. This study aims to analyze the relationship between the perceived net benefits of electronic medical records and the effectiveness of polyclinic services at Prof. Dr. Soekandar Regional General Hospital, Mojokerto Regency. The research was conducted using a quantitative approach using a cross-sectional analytical design. All 70 polyclinic staff were involved as respondents. Data were collected through questionnaires and tested for validity and reliability. The data were then analyzed descriptively and inferentially using the Spearman correlation test. The findings indicate that the perception of the benefits of EMR and the level of effectiveness of polyclinic services are mostly in the moderate category. Statistical testing confirmed a significant and positive correlation between the perceived benefits of the system and the effectiveness of services. This means that increasing the benefits of EMR tends to be followed by an increase in the effectiveness of polyclinic services. Therefore, optimizing system quality, strengthening information technology infrastructure, and improving user competency are strategic steps to maximize the utilization of EMR and improve health service performance.